Unrealistic Post-Surgical Expectation of Independence (UPSI) Predicts Complex Hospital Discharge - Chan, Chiao-Li (J Surg Res, 2018)
BACKGROUND: Careful discharge planning for older surgical patients can reduce length of stay, readmission, and cost. We hypothesized that patients who overestimate their self-care ability prior to surgery are more likely to have complex post-operative discharge planning. MATERIALS AND METHODS: The Vulnerable Elders Surgical Pathways and Outcomes Assessment (VESPA) is a brief pre-operative assessment that can identify older (age >=70) patients with multidimensional geriatric risk, defined by all three of the following: (1) physical or cognitive impairment, (2) living alone, and (3) lack of handicap-accessible home. The VESPA also asks a novel post-operative self-care ability question, whether patient can independently provide self-care for several hours after discharge. Classifying patients into four groups based on multidimensional geriatric risk (full vs none/partial) and the self-care ability question (yes/no), we hypothesized those with Unrealistic Post-Surgical expectation of Independence (UPSI) (both fully at risk + “yes” to self-care ability question ) would be at the elevated risk for complex discharge planning. Complex discharge planning was defined as prolonged stay due to nonmedical reasons or multiple changes in discharge plans. RESULTS: In 382 hospitalizations of ≥2-days, 366 had a non-missing answer to the self-care question; of those 5% had UPSI and 6.3% needed complex discharge planning. The UPSI group was independently associated with greater risk of complex discharge planning compared to the Normal group (odds ratio=4.3 [95% CI: 1.1–16.1]). CONCLUSIONS: Complex discharges were rare, but predictable by pre-operative geriatric screening. Patients with UPSI should be targeted for post-operative care planning in advance of surgery.